Empagliflozin reduces diffuse myocardial fibrosis by extracellular volume mapping: A meta-analysis of clinical studies - Wang, Haipeng; Ding, Lin; Tian, Liwen; Tian, Yutian; Liao, Lin; Zhao, Junyu (Frontiers in Endocrinology, 2022)
Objective: The aim of the study was to evaluate the effect of empagliflozin on diffuse myocardial fibrosis by cardiac magnetic resonance (CMR) T1 mapping. Research Methods & Procedures: Database including PubMed, Cochrane library, Embase and Sinomed for clinical studies of empagliflozin on myocardial fibrosis were searched. Two authors extracted the data and evaluated study quality independently. Weighted mean difference (WMD) and 95% confidence intervals (CI) were used for continuous variables. Review Manager 5.3 was used to performed the analysis. Results: Six studies were included in this meta-analysis. One of the six studies was assessed as poor quality by the assessment of methodological quality, however the rest five studies were considered good. The WMD values of △extracellular volume (ECV) was merged by fixed-effect model and the pooled effect size was -1.48 (95% CI -1.76 to -1.21, P<0.00001), that means in favor of empagliflozin. Heterogeneity analysis did not found any heterogeneity (Chi2=0.39, P=0.82, I2= 0%). In addition, empagliflozin had a tendency to reduce ECV compared to treatment before with no statistical significance (WMD=-0.29, 95% CI -1.26 to 0.67, P=0.55; heterozygosity test, Chi2=2.66, P=0.45, I2= 0%). The WMD values of △native T1 value was also merged by fixed-effect model but the pooled effect size showed neither statistical difference between empagliflozin and placebo treatment (WMD=-5.40, 95% CI -21.63 to 10.83, P=0.51) nor heterogeneity (Chi2=0.05, P=0.83, I2= 0%). Conclusions: Empagliflozin has the effect of cardiovascular benefits by reducing diffuse myocardial fibrosis. ECV could act as a noninvasive imaging tool to assess diffuse myocardial fibrosis and monitor disease progression.